Analysing Constraints to Strengthen Multi-level Inland Fisheries Cooperatives in Tamil Nadu, India - Pugazhenthi P.; Akshata Thavai; Ankush Kamble; Shivaji Argade (Journal of Indian Fisheries Association, 2024)
Inland fisheries cooperatives in Tamil Nadu face multiple challenges across institutional levels. This study identified constraints and suggested strategies to strengthen their performance by examining 40 purposively selected primary inland fisheries cooperatives—equally divided between two-tier (directly linked to the state federation) and three-tier cooperatives (linked through district and state federations). In addition, one state level federation (TAFCOFED) and two district inland fisheries federations were included. Data were gathered through focus group discussions and interviews with executive and general body members. Using the Constraint Analysis Index, constraints were classified into five major categories: financial, infrastructural, technical, social, and cooperative governance. Three-tier cooperatives were most affected by financial constraints, particularly lack of credit facilities (CAI = 100.00), followed by political interference (CAI = 91.67). In two-tier cooperatives, the most pressing issues were poor marketing infrastructure (CAI = 100.00) and poor member interest and participation (CAI = 89.00). At the district and state federation levels, poor marketing facilities, unavailability of technical support, and weak member engagement (each with CAI = 100.00) emerged as major concerns. Common challenges across all levels included limited credit access, inadequate infrastructure, and weak financial status. To address these issues, the study recommends strengthening financial linkages and working capital, upgrading market infrastructure, and enhancing water body management. It also stresses the importance of inclusive training of all the members, increased member participation, and regular, politically neutral elections to promote the sustainable development of inland fisheries cooperatives.